VD_FINDINFO AI 178/10 - 331/2012 vom 2. Oktober 2012 - VD Tribunal cantonal (2012)
AIASSURANCE, RÉVISIONPRESTATION D'ASSURANCE, ÉVALUATION DE L'INVALIDITÉ | 28 LAI, 4 LAI, 57 LAI, 16 LPGA, 17 LPGA, 43 LPGA, 6 LPGA, 7 LPGA, 8 LPGA